Review of Raynaud’s phenomenon: pathomechanisms, diagnosis and treatment - Marczyk, Aleksandra; Makowska, Karolina; Billewicz, Marta; Lis, Laura; Turek, Aleksandra; Popiołek, Adam; Pietrzykowska, Julia; Zatorska, Oksana (Journal of Education, Health and Sport, 2024)
Introduction: Raynaud’s phenomenon (RP) is a quite common but often unrecognised vasospastic condition of the peripheral vessels. This may happen after exposure to the cold, stress, vibrations or a wide range of medical conditions. It causes episodic colour changes of the digits, firstly there is a pallor, followed by cyanosis and/or redness, usually with pain. Raynaud’s phenomenon can be primary (i.e. Raynaud’s disease) or secondary (i.e. Raynaud’s syndrome) to underlying disease. Aim of the study: The aim of the study was to discuss the complex and incompletely understood pathophysiology of Raynaud’s phenomenon and to evaluate treatment approaches of both ‘uncomplicated’ - mostly primary and ‘complicated’ - mostly secondary Raynaud’s phenomenon. State of knowledge: Raynaud’s phenomenon is a common disorder with an unclear pathophysiology. Although many treatment approaches have been reported, there is still no cure or gold standard therapy. Further investigations into treatment are required. Conclusions: Future research is needed to understand the complex pathogenesis of RP and to develop optimised approaches to management.